PENGARUH TEMPERATUR KARBONASI TERHADAP KARAKTERISTIK PEMBAKARAN BRIKET SAMPAH KOTA - Dwi Aries Himawanto (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2005)
The aim of the research was find out the effect of carbonization temperature to the combustion characteristic of Municipal Solid Waste (MSW) briquette as an alternative solid fuel. The broquette manufacturing started when the MSW with contain 10 % weight of non organic matter crushed into litle pieces, limestone and mollases as a binder ,and pressed in pressing machine. The formed biobriquette were taken into a carbonization furnace to carbonize in three diferent temperature i.e. 80 0C, 120 0C, and 140 0C, then taken into furnace to find tthe combustion characterictics. The results of the research show that the 120 0C carbonize briquette give the best combustion performance .